Myeloid-Derived Suppressor Cells: A Multifaceted Accomplice in Tumor Progression - Jia-Nan Cheng; Jia-Nan Cheng; Yi-Xiao Yuan; Yi-Xiao Yuan; Yi-Xiao Yuan; Bo Zhu; Bo Zhu; Qingzhu Jia; Qingzhu Jia (Frontiers in Cell and Developmental Biology, 2021)
Myeloid-derived suppressor cell (MDSC) is a heterogeneous population of immature myeloid cells, has a pivotal role in negatively regulating immune response, promoting tumor progression, creating pre-metastases niche, and weakening immunotherapy efficacy. The underlying mechanisms are complex and diverse, including immunosuppressive functions (such as inhibition of cytotoxic T cells and recruitment of regulatory T cells) and non-immunological functions (mediating stemness and promoting angiogenesis). Moreover, MDSC may predict therapeutic response as a poor prognosis biomarker among multiple tumors. Accumulating evidence indicates targeting MDSC can reverse immunosuppressive tumor microenvironment, and improve therapeutic response either single or combination with immunotherapy. This review summarizes the phenotype and definite mechanisms of MDSCs in tumor progression, and provide new insights of targeting strategies regarding to their clinical applications.